Evaluation for Correlation of Cheiloscopy and Dermatoglyphics in Gender Determination - Tim Peter Thermadam1, Laxmikanth Chatra2, Auswaf Ahsan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Identification of the suspect, living or dead with the help of physical charachteristics play a vital role in forensic science. Improved methods of gender determination and personal identification are important in solving criminal cases. Cheiloscopy and dactyloscopy have been proved to be of use in personal identification. The present study aims to evaluate correlation of Cheiloscopy and Dermatoglyphics in gender determinationMaterials and Method: The study was carried out from January 2017 to January 2019 on 2112 individuals (1056 males and 1056 females) aged from 15 to 60 years in KMCT Dental College, Calicut. For lip print analysis Suzuki and Tsuchihashi classification was followed. For finger print analysis impression of all the fingers were taken. For analysis, the images were cropped and abode photoshop software was used.Results: Type 1 and 1’ lip groove patterns were found to be predominant among males.Type 4 and Type 5 lip groove patterns were found to be predominant among females. Loop finger print patterns were found to be predominant among males.Whorl finger print patterns were found to be predominant among females. Positive correlation (+0.80) was found between loop finger print pattern and Type 1’ lip print pattern in males which is statistically significant (p=0.003).Positive correlation (+0.75) was found between whorl finger print pattern and Type IV lip groove pattern in females which is statistically significant. (p=0.005)Conclusion: There was definite correlation of Cheiloscopy and Dermatoglyphics in gender determination